‘Economic, Education, Environment’ Pelatihan Guru TK Dan TPA Serta Bakti Sosial Di Mesjid At-Taqwa Universitas Pancasila - Sri Widyastuti; Sudarmin Parenrengi; Tia Ichwani (FEB-UP Press, 2019)
Early childhood education is the basis for the development of individual character in his future life. Teachers are not only required to master the fields of science, teaching materials, and methods, but also must be able to motivate students to have skills, be creative and have broad insights. This relates to the potential that exists in the community that has not been carried out optimally, so it requires the involvement of other parties in this case universities to provide counseling and training to the community. Therefore, there was a training and counseling activity for kindergarten and TPA teachers located at the At-Taqwa Mosque.